Effect of paracetamol as a prophylactic analgesic in infertile women undergoing hysterosalpingography in Bayelsa State, South-South Nigeria: a randomised controlled trial - Oriji, Peter Chibuzor; Kiridi, Enefia Kelvin; Ugwoegbu, Johnpatrick Uchenna; Abasi, Isaac Joel; Ubom, Akaninyene Eseme (International Journal of Clinical Trials, 2022)
Background: Hysterosalpingography is the primary investigative modality of choice for the evaluation of the uterine cavity, fallopian tubes, and adjacent peritoneal cavity. Objective were to compare the effectiveness of paracetamol and placebo in pain reduction during hysterosalpingography. Methods: This randomised controlled trial was conducted at the radiology departments and infertility clinics of the Federal Medical Centre, Yenagoa and Niger Delta University Teaching Hospital, Okolobiri, both in Bayelsa State, Nigeria, from February, 2021-July, 2021. Three hundred and eighty infertile women were assigned into two groups. Women in group I received paracetamol, while the women in group II received placebo. Data were analysed using statistical product and service solutions for Windows® version 25. Student’s t-test was used to compare sample means; and the Chi-square test was used to compare the proportion of women who expressed pain at the different steps of the procedure. Results: Pain ratings among women in the placebo group were higher than those of women in the paracetamol group at all the stages of the procedure. The highest pain scores were recorded during the instillation of contrast media in both study groups, but higher in patients in the placebo group. Conclusions: Our study revealed that paracetamol was superior to placebo in the control of hysterosalpingography-associated pain. However, pain scores high in the 2 groups during instillation of contrast media into uterine cavity.